Deciphering reprogramming efficiency in human induced pluripotent stem cells: insights from the generation of 150 cell lines - Kuebler, Bernd; Selvitella, Silvia; Aran, Begoña; Raya, Angel; Veiga, Anna (Frontiers in Immunology, 2026)
IntroductionThe discovery of induced pluripotent stem cells (iPSCs) revolutionized the field of translational medicine by enabling the reprogramming of adult somatic cells into a pluripotent state. From personalized disease models to innovative cell therapies, iPSCs are poised to play a central role in the future of clinical medicine. iPSCs hold enormous promises due to their ability to self-renew indefinitely and differentiate into all somatic cell types, thus offering patient-specific cellular models and therapeutic options without the ethical constraints of embryonic stem cells (ESCs). iPSCs, which exhibit pluripotency similar to embryonic stem cells, are generated by introducing specific factors into terminally differentiated cells, inducing a shift in their epigenetic and transcriptional landscape, which leads to the reactivation of the pluripotency program of the cells. Nevertheless, the mechanisms underlying successful reprogramming remain poorly understood.MethodsIn this study we performed a statistical evaluation of reprogramming efficiencies of 150 iPSC lines generated in our lab, comparing factors such as the starting somatic cell type, passage number, donor´s health status, donor age and sex, reprogramming methodology, and growth conditions.Results/DiscussionWe found that the most relevant factor influencing reprogramming efficiency is the developmental status of the starting cells. While other parameters may exert minor effects, inherent donor-specific biological characteristics appear to play the strongest role in determining reprogramming outcomes.